If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -3k = -5 Solving 10 + -3k = -5 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -3k = -5 + -10 Combine like terms: 10 + -10 = 0 0 + -3k = -5 + -10 -3k = -5 + -10 Combine like terms: -5 + -10 = -15 -3k = -15 Divide each side by '-3'. k = 5 Simplifying k = 5
| 3=x-2/2 | | x^4+x^9= | | 7(x+2)+2x=32 | | 5h-6p=4w^2 | | 3(4k+4)=0 | | y-2x+6= | | 15M-9=180 | | 4000lbs=tons | | 23t-7= | | x/-2x^4 | | -37-7v=-24+48 | | a/20+14/15 | | 38=6(x+4)-8x | | 6(x+8)=12 | | (y^2-5)(9y^2-4y+4)= | | 0-65=-4c | | 15x-9=6x+1 | | 5n=5n-2 | | abcx=d | | 6x-8=-4x-12 | | 500/50*3+15+8*5-4*3 | | 3y-8=-5y | | 0.8u=0.2 | | 3x=28-15x | | X-4(4+3x)=4 | | 0.8u=0.2 | | 7m/7+3m/14 | | 2i^2(9-3i)= | | -3/1/3 | | [6]+[-8]= | | .5(x+2)-.8(x+2)=-.3x-.6 | | 5(3n+1)=8(6n+9)+1 |